117 Acute inflammatory demyelinating polyneuropathy as a primary manifestation of lupus in a pregnant patient a rare and an atypical presentation. (April 2019) - Umar, Anam; Bilal, Muhammad; Umar, Bina; Chang, Eric; Elhammali, Balsam; Bradley, Cinnamon
Abstract : Background: Systemic lupus erythematosus (SLE) is associated with several neuropsychiatric syndromes involving both the central and peripheral nervous systems. These syndromes are related with SLE progression and thus, are rarely present at the onset of disease. We are reporting a rare case of acute inflammatory demyelinating polyneuropathy (AIDP) as the first manifestation of SLE in a previously asymptomatic patient. Methods: Not applicable as it is a clinical vignette The abstract for clinical vignette is uploaded as a separate document Results: Not applicable as it is a clinical vignette The abstract for clinical vignette is uploaded as a separate document Conclusions: Symptoms of AIDP frequently start in lower extremities, yet in about 10% of patients, arm or facial muscle weakness can be the initial presentation. CSF analysis typically revealed an elevated protein with a normal white cell count; however, a normal CSF protein is observed in one-third to one-half of patients when tested early in the disease course. Our patient had upper extremity weakness as well as initial negative CSF findings, which led to the delay in diagnosis. It is imperative to have a sound knowledge of the typical as well as atypical neurological manifestations of SLE to reduce the morbidity and mortality rate of patients. Funding Source(s): None